2022
DOI: 10.1039/d1cs01169c
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic applications of hydride abstraction reactions by organic oxidants

Abstract: Organic oxidants, including quinones, oxoammonium ions, and trityl cations, abstract hydride ions to form carbocations. This review describes the mechanistic foundations for these processes and the vast array of their applications in synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 222 publications
0
24
0
Order By: Relevance
“…It has been reported that heteroatom-containing substrates can be oxidized by DDQ to generate oxocarbenium or iminium ion species through a hydride abstraction mechanism. 27 Thus, hydride abstraction of THIQ 4 by DDQ in the presence of TFA forms iminium-trifluoroacetate complex Int-1 , which undergoes allylation to afford the desired product 5 . For catalytic cycle, molecular oxygen plays a critical role to form NO 2 , which could oxidize DDQH 2 back to DDQ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that heteroatom-containing substrates can be oxidized by DDQ to generate oxocarbenium or iminium ion species through a hydride abstraction mechanism. 27 Thus, hydride abstraction of THIQ 4 by DDQ in the presence of TFA forms iminium-trifluoroacetate complex Int-1 , which undergoes allylation to afford the desired product 5 . For catalytic cycle, molecular oxygen plays a critical role to form NO 2 , which could oxidize DDQH 2 back to DDQ.…”
Section: Resultsmentioning
confidence: 99%
“…A possible mechanism of the DDQ-catalyzed allylation under aerobic condition is proposed in Scheme . It has been reported that heteroatom-containing substrates can be oxidized by DDQ to generate oxocarbenium or iminium ion species through a hydride abstraction mechanism . Thus, hydride abstraction of THIQ 4 by DDQ in the presence of TFA forms iminium-trifluoroacetate complex Int-1 , which undergoes allylation to afford the desired product 5 .…”
Section: Resultsmentioning
confidence: 99%
“…15 We envisioned that changing the oxidative C−H bond-cleavage pathway from HAT to direct hydride abstraction would be beneficial to diastereoselective reaction design. 13 Common organic hydride abstracting agents include quinones, oxoammonium ions, and triarylmethyl (trityl) cations. 16 Accordingly, these three types of hydride abstracting agents have been comprehensively explored during the methodology development process.…”
Section: Diastereoselective Intermolecular Oxidative C−h Functionaliz...mentioning
confidence: 99%
“…), and long reaction times, all of which are generally disadvantageous for achieving stereoselective variants . We envisioned that changing the oxidative C–H bond-cleavage pathway from HAT to direct hydride abstraction would be beneficial to diastereoselective reaction design …”
Section: Hydride-abstraction-initiated Diastereoselective Intermolecu...mentioning
confidence: 99%
“…Based on the known ability of lithium amides (e.g., 1 ) to undergo imine formation (e.g., 2 ) upon reducing simple ketones, , a process that we have found to be rapid for lithium amides derived from alicyclic amines, we recently developed a new strategy for amine α-C–H bond functionalization (Scheme d) . Various α-functionalized amines can be accessed with this approach.…”
mentioning
confidence: 99%